Unusual cold rolled texture in an Mg-2.0Zn-0.8Gd sheet. (15th January 2017) - Luo, J.; Hu, W.W.; Jin, Q.Q.; Yan, H.; Chen, R.S.
Abstract: The Mg-2.0Zn-0.8Gd (wt%) sheet with double peak transverse direction (TD) tilted non-basal texture was cold rolled, and obtain a new texture, named as elliptical annular texture, rather than the traditional basal texture. In addition, the maximum texture intensity of the cold rolled samples decreased with the increased accumulated reductions. The formation of this unusual texture was attributed to the initial non-basal texture and multiple deformation modes. Graphical abstract: